Strategies for international market expansion: Strength, Weakness, Opportunity and Threat (SWOT) attributes of Malaysian construction firms / Che Maznah Mat Isa, Hamidah Mohd Saman and Christopher Nigel Preece - Mat Isa, Che Maznah; Mohd Saman, Hamidah; Preece, Christopher Nigel (Universiti Teknologi MARA, Perlis, 2014)
The competitive and saturated construction industry has led many domestic firms to expand internationally. Therefore, in today’s global industry, the construction firms must adopt a superior and an effective strategy to endure the increasing dynamics and uncertainties in the foreign markets. In the early stage of strategic planning, one of the basic but important steps is the need for firms to identify their strength, weakness, opportunity and threat (SWOT) attributes before they expand internationally. The aim of this study is to identify the important SWOT attributes to help the firms to manage and ease the inherent complexities and difficulties within international market domain. Survey questionnaires were sent to 115 Malaysian construction firms listed under Construction Industry Development Board Malaysia 2013 record resulted in 48.7 percent response rate. The relative importance index (RII) was used to rank the SWOT attributes. The findings revealed the following highest ranking of SWOT attributes: the ability to produce good quality products/services (strength), lack of research and development (weakness), mergers (opportunity), and policies, laws and regulations of host country (threat). The correlation analysis reveals a strong positive relationship between the opportunity and the threat attributes which indicates that the abundant opportunities are also accompanied by the inherent threats in the international markets. Thus, this study illustrates the identification of the most significant SWOT attributes related to the firms’ international operations. It is hoped that the findings would offer valuable information and practical guidance to construction firms in their preparatory works to internationalize.